Resequencing Data Indicate a Modest Effect of Domestication on Diversity in Barley: A Cultigen With Multiple Origins. (11th December 2013) - Morrell, Peter L.; Gonzales, Ana M.; Meyer, Kapua K.T.; Clegg, Michael T.
Abstract: The levels of diversity and extent of linkage disequilibrium in cultivated species are largely determined by diversity in their wild progenitors. We report a comparison of nucleotide sequence diversity in wild and cultivated barley ( Hordeum vulgare ssp . spontaneum and ssp. vulgare ) at 7 nuclear loci totaling 9296bp, using sequence from Hordeum bulbosum to infer the ancestral state of mutations. The sample includes 36 accessions of cultivated barley, including 23 landraces (cultivated forms not subject to modern breeding) and 13 cultivated lines and genetic stocks compared to either 25 or 45 accessions of wild barley for the same loci. Estimates of nucleotide sequence diversity indicate that landraces retain >80% of the diversity in wild barley. The primary population structure in wild barley, which divides the species into eastern and western populations, is reflected in significant differentiation at all loci in wild accessions and at 3 of 7 loci in landraces. "Oriental" landraces have slightly higher diversity than "Occidental" landraces. Genetic assignment suggests more admixture from Occidental landraces into Oriental landraces than the converse, which may explain this difference. Based on θπ for silent sites, modern western cultivars have ~73% of the diversity found in landraces and ~71% of the diversity in wild barley.